Fourier transform infrared spectroscopy of dental unit water line biofilm bacteria. Issue 3 (2009) - Liaqat Liaqat, Iram Iram
Abstract : Fourier transform-infrared (FT-IR) spectroscopy has become an important tool for rapid analysis of complex biological samples. The infrared absorbance spectrum could be regarded as a "fingerprint" which is a feature of biochemical substances. The FT-IR spectra of fresh and stored dried samples of six bacterial isolates ( Klebsiella sp., Bacillus cereus, Bacillus subtilis, Pseudomonas aeruginosa, Achromobacter xylosoxidans and Achromobacter sp.) were observed by variation in sample preparation. The results indicated that variation in sample preparation did not affect the spectra of isolates. However, less promiment/absence of a small shoulder peak at 1738 cm −1 was evident in fresh dried samples of Achromobacter sp. and A. xylosoxidans compared to prominent and broad shoulder band at 1724 cm −1 in stored dried samples of these two isolates. In addition to the established KBr pellet technique, attenuated total reflectance (ATR) spectroscopy was used to analyse the spectra of planktonic growth (−80°C liquid cultures) and biofilm growth of six isolates. ATR spectroscopy of −80°C planktonic and biofilm growth showed variation in absorption spectra in fingerprint (1200−900 cm −1 ) region. Two clear absorption bands were prominent in biofilm at 1175 and 1143 cm −1 whereas, one prominent broad band at 1075 cm −1 resulting from the overlapping of two band was noted in planktonic cultures. Biofilm forming capability of the six isolates was also determined by acridine orange staining method. The microscopic analysis of biofilms formed on glass slides revealed the presence of a matrix of exopolysaccharides and microcolonies typical of biofilm architecture. Maximum biofilm formation was observed after 175 h in P. aeruginosa and Klebsiella sp.